The influence of entrepreneurship learning and entrepreneurial motivation on young entrepreneurial interest in a Buddhist college - Gusnadi, Gunawan; Ardianto, Hendri; Rapiadi (Ifma Publishing, 2024)
This research aims to analyze the influence of entrepreneurship learning and entrepreneurship motivation on entrepreneurial interest among students. The research method used is a survey with a quantitative approach. The research population is 150 students in the Business and Management Program at the Buddhist College in Indonesia. Sampling was done using the Slovin formula, resulting in a sample size of 109. The collected data was analyzed using multiple linear regression to identify the influence of entrepreneurship learning and entrepreneurship motivation on the interest of young entrepreneurs. The findings show that entrepreneurship learning and entrepreneurship motivation have a significant influence on students' interest in becoming young entrepreneurs. This discovery has significant implications for the development of education and entrepreneurship development programs at universities to encourage students' interest and participation in entrepreneurship.